Towards Blockchain Developer Experience (BcDEx): Exploring Dimensions of Developer Experience in Blockchain-oriented Software Engineering - Soares, Pamella; Araújo, Allysson Allex; Saraiva, Raphael; Souza, Jerffeson (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de Software, 2024)
The Developer Experience (DEx) in the context of blockchain and decentralized applications has to deal with new or adapted software engineering practices due to the particular characteristics of these technologies. This study proposes the idea of Blockchain Developer Experience (BcDEx) influenced by different practices of Blockchain-Oriented Software Engineering (BOSE). To achieve this purpose, we categorize and discuss critical BcDEx factors based on a well-established DEx conceptual framework covering cognitive, affective, and conation dimensions. Furthermore, we reveal new directions that can benefit both research and practice in BcDEx, encompassing practical aspects such as using technical resources and organizational considerations.